2021
DOI: 10.3389/fimmu.2021.677824
|View full text |Cite
|
Sign up to set email alerts
|

PSGL-1 Is a T Cell Intrinsic Inhibitor That Regulates Effector and Memory Differentiation and Responses During Viral Infection

Abstract: Effective T cell differentiation during acute virus infections leads to the generation of effector T cells that mediate viral clearance, as well as memory T cells that confer protection against subsequent reinfection. While inhibitory immune checkpoints have been shown to promote T cell dysfunction during chronic virus infections and in tumors, their roles in fine tuning the differentiation and responses of effector and memory T cells are only just beginning to be appreciated. We previously identified PSGL-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
10
2
Order By: Relevance
“…Since Selplg -/- P14 + T cells drastically declined during Cl13 infection compared to WT T cells and we observed no differences between their proliferation suggests that Selplg -/- P14 + T cells had a decreased ability to survive, which could also be explained by their diminished Tpex population. This contrasts with what was observed in Selplg -/- mice infected with Arm or Cl13 where T cell survival was increased, in part due to the viral clearance that occurs in Selplg -/- infected mice ( 8 , 38 ). The importance of immune checkpoints in T cell differentiation was also highlighted in studies using WT and Selplg -/- SMARTA + and P14 + T cells transferred in WT Arm infected mice, which showed that even though more memory Selplg -/- TCR transgenic T cells developed, they failed to be recalled during a secondary infection ( 38 ).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Since Selplg -/- P14 + T cells drastically declined during Cl13 infection compared to WT T cells and we observed no differences between their proliferation suggests that Selplg -/- P14 + T cells had a decreased ability to survive, which could also be explained by their diminished Tpex population. This contrasts with what was observed in Selplg -/- mice infected with Arm or Cl13 where T cell survival was increased, in part due to the viral clearance that occurs in Selplg -/- infected mice ( 8 , 38 ). The importance of immune checkpoints in T cell differentiation was also highlighted in studies using WT and Selplg -/- SMARTA + and P14 + T cells transferred in WT Arm infected mice, which showed that even though more memory Selplg -/- TCR transgenic T cells developed, they failed to be recalled during a secondary infection ( 38 ).…”
Section: Discussioncontrasting
confidence: 82%
“…This contrasts with what was observed in Selplg -/- mice infected with Arm or Cl13 where T cell survival was increased, in part due to the viral clearance that occurs in Selplg -/- infected mice ( 8 , 38 ). The importance of immune checkpoints in T cell differentiation was also highlighted in studies using WT and Selplg -/- SMARTA + and P14 + T cells transferred in WT Arm infected mice, which showed that even though more memory Selplg -/- TCR transgenic T cells developed, they failed to be recalled during a secondary infection ( 38 ). A similar phenotype in defective memory differentiation was also observed in PD-1-deficient T cells responding to respiratory viral infection ( 43 ).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Regarding the adaptive immune system, we found a high proportion of effector memory and terminally differentiated subpopulations, decreased CD226 expression and high CD162 expression in CD4 + T cells in severe patients. The CD162 (PSGL-1) has been described by having a role in inducing T cell exhaustion and driving effector and memory in T cells during acute infection [ 36 , 37 , 38 ]. The involvement of this receptor in the changes of T cell memory profile and the effect of its blockade in T cell function of COVID-19 patients should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to healthy control participants, histopathological confirmation revealed an increase in parenchymal CD163 + microglia/ macrophages paralleled by increased expression of PSGL-1. Despite being considered a T cell immune checkpoint [ 41 , 42 ], PSGL-1 has been shown to aid in the spreading and metastasis of melanoma and colon cancer cells via P-selectin (SELP) mediated platelet activation [ 43 , 44 ]. In glioblastoma, cancer cells overexpress and oversecrete SELP to exploit PSGL-1 signaling in glioma-associated microglia/macrophages.…”
Section: Discussionmentioning
confidence: 99%